The Relationship Between Illusory Heaviness Sensation and the Motion Speed of Visual Feedback in Gesture-Based Touchless Inputs - Kawabe, Takahiro; Ujitoko, Yusuke; Yokosaka, Takumi (Frontiers in Psychology, 2022)
Interaction systems with gesture-based touchless inputs are becoming more common. Nevertheless, perceptual properties of the visual feedback used in the system have not been well documented. We investigated whether the speed of motion shown in visual feedback used in gesture-based touchless inputs could be a cue for the heaviness sensation of an object even when other incidental cues, such as changes in object size and spatial consistencies in direction between gestures and feedback, were eliminated from the stimuli. Participants were asked to make a gesture to grasp and raise/lower disks shown on a horizontal display. The disk’s diameter changed in accordance with the vertical position of the participant’s hand. The results showed that the rate of change in diameter determined the heaviness sensation. When the disks were replaced with concentric gratings having sinusoidal radial intensity and thus the cue of size change was eliminated from the stimuli, the heaviness sensation was dependent on the speed of phase shift (that is, motion) in the grating. It was also found that spatial consistency between the direction of gestures and phase shift was not a critical condition for the heaviness sensation. Finally, the speed of motion served as a critical determinant of the heaviness sensation even when another visual feature (i.e., frame rate) was modulated in a single session, which indicates that the effect of the speed of motion on the heaviness sensation was unlikely due to demanded characteristics. The results indicate that the heaviness sensation for visual feedback of gesture-based touchless inputs is based purely on the speed of the visual feedback motion.